Preparation method and application of magnesium boride two-dimensional sheet material
By ultrasonic treatment of magnesium boride particles in absolute ethanol, 1-butanol and sodium chloride solution at room temperature, the problem of high-power ultrasound and low temperature required to prepare magnesium boride two-dimensional nanosheets in the existing technology is solved. A simple, safe and efficient preparation method has been achieved, with high hydrogen production and suitable for arthritis treatment.
Patent Information
- Application Number
- CN202411648582.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art requires high-power ultrasonic equipment and low-temperature conditions when preparing magnesium bored two-dimensional nanosheets, and the process is complex, making it difficult to achieve a simple, safe and efficient preparation method.
Add magnesium boride particles to absolute ethanol, add 1-butanol dropwise, and add sodium chloride solution, stir and ultrasonic treatment, and achieve two-dimensional sheets obtained by peeling off magnesium boride at room temperature, low ultrasonic power, and in a short time. shape material.
This method realizes the simple and efficient preparation of magnesium boride two-dimensional sheet materials at room temperature and without the need for inert environmental conditions. It has high hydrogen production, good safety, and is suitable for clinical applications.
Smart Images

Figure CN119160905B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a preparation method and application of a two-dimensional magnesium boride sheet material. Background Art
[0002] Arthritis is a common chronic disease characterized by joint inflammation, pain, swelling and limited mobility. Osteoarthritis is the most common type of arthritis, characterized by the degeneration of articular cartilage and bone hyperplasia at the joint margins. Currently, the treatment of arthritis usually includes medication, physical therapy and surgical treatment. Among drug treatments, nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used drugs, but long-term use may cause side effects in the gastrointestinal tract and cardiovascular system. Therefore, the development of new, safe and effective treatments for arthritis is of great clinical significance.
[0003] In the field of materials science, two-dimensional (2D) materials have attracted extensive attention due to their unique physical and chemical properties. Magnesium boride (MgB2) is a material with superconducting properties. In recent years, researchers have begun to explore its potential for application in the biomedical field. MgB2 has high chemical stability and biocompatibility, which makes it a potential application prospect in drug delivery, tissue engineering and biosensors.
[0004] As a high-quality energy carrier, hydrogen can not only be used in medical treatment, health care and beauty, but also is a very important industrial raw material. It is widely used in petroleum, chemical industry, electronics, metallurgy, oil, aerospace, light industry and other fields. Hydrogen has extremely high biosafety, so hydrogen is gradually being used in medicine. Studies have shown that hydrogen has obvious therapeutic effects on diseases including cancer, diabetes, stroke, atherosclerosis, Parkinson's disease, Alzheimer's disease (AD), arthritis, etc. However, there are relatively few hydrogen-producing materials at present, and safe and efficient hydrogen-producing materials are of great value for further application and research exploration. The patent with application number CN202211262260.7 discloses a method for preparing a hydrogen-producing material and the obtained hydrogen-producing material and application, using magnesium boride particles as hydrogen-producing materials, but compared with nanoparticles, magnesium boride two-dimensional nanosheets of the same mass have a larger contact area and can produce more hydrogen. At present, magnesium boride two-dimensional nanosheets are mainly prepared by ultrasonic exfoliation methods, such as Inert Liquid Exfoliation and Langmuir-Type Thin Flim Deposition of Semimetallic Metal Diborides (Kevin Synnatschke et al., ACS NANO, 2024), which proposed an ultrasonic-assisted liquid exfoliation method under inert conditions to produce quasi-two-dimensional nanosheets with intrinsic material properties. However, this method is relatively complicated and the conditions are relatively harsh, and it must be carried out at 10°C. The patent with application number CN202211056597.2 discloses a method for preparing magnesium boride nanosheets and its application in Li-S battery separators. Magnesium boride powder is added to NMP and ultrasonically exfoliated at 0°C for 1 h using a cell disruptor. This method uses an ultrasonic disruptor with an ultrasonic power of 150~200 W. Not only is the ultrasonic power large, but the exfoliation is carried out at 0°C and the conditions are harsh. Therefore, a simple method for preparing magnesium boride two-dimensional sheet materials is needed, which does not require high-power ultrasonic equipment, has loose preparation conditions, and can easily exfoliate magnesium boride to obtain two-dimensional sheet materials by a simple method. Summary of the invention
[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a preparation method and application of magnesium boride two-dimensional sheet material. In the present invention, magnesium boride particles are added to anhydrous ethanol, and then 1-butanol is added dropwise and a sodium chloride solution is added, so that the magnesium boride particles can be peeled off at room temperature, very low ultrasonic power and very short ultrasonic time to obtain a magnesium boride two-dimensional sheet material. The method of the present invention can be carried out at room temperature, without the need for an inert environment, and can easily ultrasonically peel magnesium boride to obtain a two-dimensional sheet material.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a method for preparing a two-dimensional sheet material of magnesium boride, the preparation method comprising:
[0008] The magnesium boride powder is ground to obtain magnesium boride particles, the magnesium boride particles are added to anhydrous ethanol, and then 1-butanol is added dropwise to form a suspension, a sodium chloride solution is added to the suspension, the suspension is stirred, and finally an ultrasonic treatment is performed to obtain a magnesium boride two-dimensional sheet material.
[0009] Preferably, the ratio of the added amounts of the magnesium boride particles, anhydrous ethanol and 1-butanol is 500 mg:50 mL:5 mL.
[0010] Preferably, the dropping speed of the 1-butanol is 0.1 mL / min.
[0011] Preferably, the ratio of the added amount of the magnesium boride particles to the sodium chloride solution is 0.1 g:1 mL.
[0012] Preferably, the mass concentration of the sodium chloride solution is 0.9%.
[0013] Preferably, the stirring is performed at room temperature for 30 min.
[0014] Preferably, the power of the ultrasound is 10 W; and the time of the ultrasound is 10 min.
[0015] The second aspect of the present invention provides a magnesium boride two-dimensional sheet material obtained by the above preparation method, wherein the size of the magnesium boride two-dimensional sheet material is 30 nm~5μm; in a neutral environment, the cumulative hydrogen production of 100 μg / ml magnesium boride two-dimensional sheet material is 2618608 μmoL / L; in an acidic environment, the cumulative hydrogen production of 100 μg / ml magnesium boride two-dimensional sheet material is 5040495 μmoL / L.
[0016] The third aspect of the present invention provides the use of magnesium boride two-dimensional sheet material in the preparation of drugs for treating arthritis.
[0017] Beneficial effects of the present invention:
[0018] (1) The present invention adds magnesium boride particles to anhydrous ethanol, then drips 1-butanol and adds sodium chloride solution, so that the magnesium boride particles can be peeled off at room temperature, very low ultrasonic power and very short ultrasonic time to obtain a two-dimensional sheet material of magnesium boride. The reagents used in the preparation process are environmentally friendly and meet the requirements of green chemistry. The method of the present invention can be carried out at room temperature, without the need for an inert environment, and can easily ultrasonically peel magnesium boride to obtain a two-dimensional sheet; the preparation process is simple, the cost is low, and it is conducive to the promotion of clinical applications.
[0019] (2) The two-dimensional sheet material prepared by the present invention has a large amount of hydrogen and high safety. Compared with traditional drug treatment, the two-dimensional sheet material prepared by the present invention does not cause liver and kidney toxicity. The material can directly play a therapeutic role at the site of inflammation, thereby improving the therapeutic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : SEM scanning electron microscopy results of the magnesium boride two-dimensional sheet prepared in Example 1, wherein (a) the scale bar is 2 μm for the magnesium boride electron microscopy image, and (b) the scale bar is 200 nm for the magnesium boride electron microscopy image;
[0021] Figure 2 : Two-dimensional scanning mapping of magnesium boride prepared in Example 1, including (a) SEM of magnesium boride, (b) element fusion map of magnesium boride, (c) distribution of magnesium element in magnesium boride, (d) distribution of boron element in magnesium boride;
[0022] Figure 3 : Atomic force microscope (AFM) images of the magnesium boride two-dimensional sheet prepared in Example 1, wherein (a) AFM image, (b) quantitative image, and (c) stereo image;
[0023] Figure 4 : XRD crystal diffraction of the two-dimensional sheet of magnesium boride prepared in Example 1;
[0024] Figure 5 : Hydrogen production performance of the magnesium boride two-dimensional sheet prepared in Example 1, wherein (a) hydrogen production rate, (b) cumulative concentration of hydrogen production;
[0025] Figure 6 : Electron micrographs of the magnesium boride prepared in Comparative Examples 1 to 3, wherein (a) an electron micrograph of the magnesium boride of Comparative Example 1, (b) an electron micrograph of the magnesium boride of Comparative Example 2, and (c) an electron micrograph of the magnesium boride of Comparative Example 3;
[0026] Figure 7 : The cytotoxicity of the magnesium boride two-dimensional sheet material prepared in Example 1, including (a) the survival rate of ATCD5 cells, (b) the survival rate of RAW264.7 cells;
[0027] Figure 8 : Example 1 prepared a magnesium boride two-dimensional sheet material to reduce the intracellular ROS level, including (a) the ROS level of ATCD5 cells, (b) the ROS level of RAW264.7 cells;
[0028] Fig. 9: The ability to treat arthritis in rats, including (a) changes in the fiber filament prickling value of each group, (b) the fiber filament prickling value of each group on the 11th day of modeling, (c) changes in the heat pain value of each group, (d) the heat pain value of each group on the 11th day of modeling, (e) changes in body weight of each group, (f) body weight of each group on the 11th day of modeling;
[0029] Fig.10 : Morphological observation, including (a) pathological tissue staining images of each group, (b) MRI images of knee joints of each group, and (c) images of articular cartilage of each group;
[0030] Fig.11 : Immunohistochemistry of pathological tissue sections, including (a) immunohistochemical pathological images of each treatment group, (b) relative expression of MMP13 in each treatment group, (c) relative expression of IL-1β in each treatment group, and (d) relative expression of ColⅡ in each treatment group. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0032] As introduced in the background technology section, the current ultrasonic exfoliation process for preparing magnesium boride two-dimensional sheet materials must not only be performed at low temperatures, but also require high ultrasonic power and long time.
[0033] Based on this, the purpose of the present invention is to provide a preparation method and application of magnesium boride two-dimensional sheet material. The present invention adds magnesium boride particles to anhydrous ethanol and performs ultrasound. However, only adding magnesium boride particles to the solvent for ultrasound still requires high-power, long-term, and even low-temperature ultrasound to achieve the peeling of magnesium boride. After research, adding 1-butanol to the anhydrous ethanol to which magnesium boride particles are added can not only further dilute the concentration of magnesium boride, but also further disperse and depolymerize magnesium boride particles. Then, sodium chloride solution is added to destroy the electrostatic force between MgB2 layers. Sodium chloride can also reduce the electrostatic force between magnesium boride particles, reduce particle aggregation, and facilitate ultrasonic peeling. The method of the present invention allows magnesium boride particles to be carried out at room temperature, and it is found during the experiment that the magnesium boride two-dimensional sheet material is not oxidized when ultrasonic peeling is not performed in an inert environment, and the hydrogen production is still very high. The maximum power of ultrasound is only 10 w, and the magnesium boride two-dimensional sheet material can be obtained by ultrasound for 10 min.
[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0035] Note: The magnesium boride of the present invention is also called magnesium diboride.
[0036] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0037] Example 1: Preparation of two-dimensional magnesium boride sheet material
[0038] Magnesium boride powder was ground for 30 minutes using a planetary ball mill to obtain magnesium boride particles. 0.5 g of magnesium boride particles were placed in 50 mL of anhydrous ethanol, and 5 mL of 1-butanol was added at a rate of 0.1 mL / min. After stirring evenly, 5 mL of 0.9% NaCl solution was added, stirred for 30 minutes, and then ultrasonicated for 10 minutes (ultrasonication for 3 s, stop for 2 s) using an ultrasonic instrument, with an ultrasonic power of 10 W. After the ultrasonication, the precipitate was filtered and washed with ultrapure water three times to obtain a two-dimensional sheet material of magnesium boride.
[0039] Example 2: Characterization
[0040] The magnesium boride two-dimensional sheet material prepared in Example 1 was subjected to scanning electron microscopy (SEM), elemental surface mapping, atomic force microscopy (AFM) and XRD analysis. The results are shown in Figure 1~Figure 4 .
[0041] like Figure 1 As shown, it can be seen that the method of Example 1 prepares a two-dimensional magnesium boride sheet, indicating that the method of the present invention can effectively peel off magnesium boride particles, and the size range of the two-dimensional magnesium boride sheet is about 30 nm~5 μm. Figure 2 From the elemental scanning mapping diagram, it can be seen that the spectrometer selected the flake structure to scan the Mg element and the B element respectively. The results showed that the flake structure was indeed MgB2. Figure 3 Atomic force microscopy (AFM) results show that the thickness of the magnesium boride two-dimensional sheet is about 320 nm, and the diameter of the sheet structure is about 2 μm. Figure 4 The X-ray diffraction (XRD) showed four strongest peaks at 33.482°, 42.411°, 51.884° and 59.884°, corresponding to (100), (101), (002) and (110) of MgB2 (PDF#38-1369), indicating that the crystal phase and composition of the MgB2 raw material have not been changed. The crystal plane height ratio determines that it has a lamellar structure.
[0042] Example 3: Hydrogen production performance of two-dimensional magnesium boride sheet material
[0043] 5 mg of the MgB2 two-dimensional sheet material prepared in Example 1 was weighed and dissolved in 50 mL of 0.9% saline at different pH values (6.0, 7.0) to obtain a 100 μg / mL MgB2 two-dimensional sheet material solution. The hydrogen production performance was tested using a UNISENSE hydrogen production microelectrode (fx-3 UniAmp). The real-time dynamic process of the concentration of hydrogen produced over time was recorded. The results are shown in Figure 5 . It can be seen that in an acidic environment, the hydrogen production of the MgB2 two-dimensional sheet material is significantly improved, indicating that the MgB2 two-dimensional sheet material prepared in Example 1 is an acid-responsive material. The cumulative hydrogen production of 100 μg / ml of the two-dimensional magnesium boride material measured in physiological saline with a pH of 7.0 was 2618608 μmoL / L; the cumulative hydrogen production of 100 μg / ml of the two-dimensional magnesium boride material measured in physiological saline with a pH of 6.0 was 5040495 μmoL / L.
[0044] Comparative Example 1
[0045] Magnesium boride powder was ground for 30 min using a planetary ball mill to obtain magnesium boride particles. 0.5 g of magnesium boride particles were placed in 50 mL of anhydrous ethanol, and then ultrasonicated for 10 min (ultrasonication for 3 s, stop for 2 s) using an ultrasonicator with an ultrasonic power of 10 W. After the ultrasonication, the precipitate was filtered and washed with ultrapure water three times to obtain magnesium boride particles.
[0046] The electron microscope image is as follows Figure 6 As shown in (a), it can be seen that when only magnesium boride particles are added to anhydrous ethanol for ultrasonic treatment, under the same ultrasonic power and time, agglomerated magnesium boride is obtained, and no magnesium boride two-dimensional sheets are obtained.
[0047] Comparative Example 2
[0048] Magnesium boride powder was ground for 30 min using a planetary ball mill to obtain magnesium boride particles. 0.5 g of magnesium boride particles were placed in 50 mL of anhydrous ethanol, and 5 mL of 1-butanol was added dropwise at a rate of 0.1 mL / min. After stirring evenly, an ultrasonic instrument was used for ultrasonication for 10 min (ultrasonication for 3 s, stop for 2 s), and the ultrasonic power was 10 W. After the ultrasonication, the precipitate was obtained by suction filtration, and the precipitate was purified by ultrapure water three times to obtain magnesium boride particles.
[0049] The electron microscope image is as follows Figure 6 As shown in (b), although the magnesium boride particles are not agglomerated together, only a small amount of magnesium boride is exfoliated.
[0050] Comparative Example 3
[0051] Magnesium boride powder was ground with a planetary ball mill for 30 minutes to obtain magnesium boride particles. 0.5 g of magnesium boride particles were placed in 50 mL of anhydrous ethanol, and a 0.9% NaCl solution was added, stirred for 30 minutes, and then ultrasonicated for 10 minutes (ultrasonication for 3 seconds, stop for 2 seconds) with an ultrasonic power of 10 W. After the ultrasonication, the precipitate was filtered and washed with ultrapure water three times to obtain a small amount of magnesium boride flakes. The electron microscope image is shown below. Figure 6 As shown in (c), the magnesium boride particles were not completely exfoliated and some particles still existed.
[0052] According to Comparative Examples 1 to 3, it can be seen that in Comparative Example 1, no NaCl solution was added, and the magnesium boride obtained after ultrasound was still agglomerated. In Comparative Example 2, 1-butanol was added, and the magnesium boride particles did not agglomerate into sheets, but a small amount of two-dimensional sheets were obtained by peeling, indicating that 1-butanol had a depolymerization effect on the magnesium boride particles. In Comparative Example 3, NaCl solution was added, and some two-dimensional sheets of magnesium boride appeared after ultrasound, but magnesium boride particles still existed, indicating that NaCl not only destroyed the electrostatic force between MgB2 layers, but also reduced the electrostatic force between magnesium boride particles and reduced particle aggregation.
[0053] Experimental Example 1: Biocompatibility Testing of Magnesium Boride Two-Dimensional Materials
[0054] 2.88 mg of the magnesium boride two-dimensional material prepared in Example 1 was weighed and added to 7.2 ml of DMEM culture medium to prepare a 400 μg / ml magnesium boride solution, which was placed in a 37°C incubator for 12 h to obtain a magnesium boride two-dimensional sheet solution. Then, DMEM was used to gradiently dilute the magnesium boride two-dimensional sheet solution to different concentrations of 400, 200, 100, 50, and 25 μg / ml.
[0055] MTT was used to detect the toxic effect of magnesium boride two-dimensional sheet solution on ATCD5 and RAW264.7 cells (both purchased from Meisen CTCC Cell Standard Supply Center).
[0056] Specific experimental steps: The experiment was divided into blank group, control group and drug group. Drug group: Cells were plated and ATDC5 and RAW264.7 cells were plated at 1×10 4The number of cells was plated on a 96-well plate, with 100 μL of cell suspension in each well. The 96-well plate was placed in a 37°C, 5% CO2 incubator for 12 h. After the cells adhered to the wall, the cell supernatant was aspirated and 100 μL of different concentrations of magnesium boride solution was added. The difference between the blank group and the drug group was that no cells were added, and the magnesium boride solution was replaced with an equal volume of DMEM; the difference between the control group and the drug group was that the magnesium boride solution was replaced with an equal volume of DMEM. The above three groups were incubated in the incubator for 24 h, the magnesium boride solution or DMEM was aspirated, and 10 μL of MTT and 90 μL of DMEM mixture were added to each well. After incubation in a 37°C, 5% CO2 incubator for 4 h, the supernatant was discarded, 150 μL / well DMSO was added, and the mixture was mixed at room temperature at 100 rpm for 10 min. The OD value of the 96-well plate was measured at wavelengths of 490 nm and 570 nm using an enzyme reader. The results are shown in Figure 7 .
[0057] Cell survival rate = (OD drug group-OD blank group) / (OD control group-OD blank group) × 100%.
[0058] according to Figure 7 It can be seen that the biological survival rate of RAW264.7 and ATDC5 cells is greater than 80%, indicating that the magnesium boride solution with a concentration range of 25-200 μg / ml has good biocompatibility. The cell survival rate of some drug groups with concentrations is greater than 100%, which may be related to the hydrogen production of magnesium boride, which promotes cell proliferation.
[0059] Experimental Example 2: Antioxidant properties of magnesium boride two-dimensional materials
[0060] The DCFH-DA molecular probe was used to detect the intracellular ROS level. The experiment was divided into 7 groups: normal group, H2O2 group, and magnesium boride solution group (using the magnesium boride prepared in Example 1, 400, 200, 100, 50, 25 μg / ml).
[0061] 8×10 4RAW264.7 and ATDC5 cells were seeded in 96-well plates at a density of 1:1 / mL and cultured overnight at 37°C and 5% CO2. When the cells grew to a density of more than 80%, the original culture medium was discarded. Then, 100 μL DMEM culture medium was added to the normal group and H2O2 group and incubated at 37°C in the dark for 24 h; 100 μL of each concentration of magnesium boride solution was added to the magnesium boride solution group (400, 200, 100, 50, 25 μg / ml) and incubated at 37°C in the dark for 24 h. Except for the normal group, which added an equal amount of DMEM culture medium (100 μL), all other groups added 100 μL of 0.5mM H2O2 solution and incubated at 37°C in the dark for 0.5 h. After that, each group was washed with PBS three times, and DCFH-DA probe diluted with DMEM medium at a final concentration of 4 μM was added, incubated at 37°C for 20 min, and washed three times with PBS. The washing process was protected from light to fully remove DCFH-DA that did not enter the cells. The fluorescence intensity was detected by a fluorescence microplate reader, with an excitation light of 488 nm and an emission light of 525 nm; the OD value of each group of probes was detected, and the ability of magnesium boride solution to scavenge reactive oxygen species at the cellular level was tested.
[0062] according to Figure 8 It can be seen that the ROS level was the highest in the H2O2 group. The ROS level in the magnesium boride solution group was significantly reduced, and it had the ability to significantly reduce the active ROS in ATDC5 and RAW264.7 cells, indicating that the magnesium boride two-dimensional sheet has a very good antioxidant effect.
[0063] Test Example 3: Animal Experiment
[0064] Experimental materials and animal grouping: The experimental animals were 160-220 g SD male rats (the rats and the bedding and maintenance feed used were purchased from Jinan Pengyue Animal Breeding Co., Ltd.). The experiment was divided into three groups: normal group (Normal), model group (KOA), magnesium boride two-dimensional tablet group (magnesium boride prepared in Example 1 was added to 0.9% physiological saline to prepare, 100 μg / mL), with 5 SD male rats in each group.
[0065] SD male rats were adaptively raised in an SPF animal room for 7 days, with sufficient food and drinking water every day and the room temperature controlled at around 22°C, and then modeling was carried out.
[0066] Arthritis model construction: 20 μL of saline was injected into the right knee joint cavity of rats in the normal group. The rats in the other groups were modeled on day 0, and the purchased rats were kept in cages in the SPF animal room. The rats were fed with sufficient drinking water and rat maintenance feed every day, and the room temperature was kept appropriate. The rat KOA model was established after the rats adapted to the environment. A 50 mg / mL MIA solution was prepared, and MIA was dissolved in saline. It was prepared and used immediately, and stored in the dark. A certain mass of magnesium boride was weighed and diluted to 100 μg / mL with saline. Sodium pentobarbital with a concentration of 40 mg / kg was injected intraperitoneally. After the rats were anesthetized, the ear tags were fixed on the right ears of the mice with ear tag clamps for marking, and then the hair at the right knee joint was shaved with a razor and disinfected with alcohol cotton balls. The depression on the outside of the patellar ligament of the rat was found, and 20 μL of MIA solution was injected into the depression. During the injection, the insulin needle was prevented from penetrating the joint cavity.
[0067] The day before modeling was recorded as -1 day, and the basal pain threshold (mechanical pain threshold) of each group of mice was tested to ensure that each group of rats were normal rats without arthritis. On the 3rd day of modeling, rats with significantly reduced mechanical pain threshold were considered to have successfully modeled, and rats with no reduced mechanical pain threshold were excluded. Ten rats with successfully modeled rats were divided into two groups: the model group (KOA) and the magnesium boride group, with 5 rats in each group.
[0068] After the model was successfully established, the rats were treated with intraarticular injections on the 4th, 6th, 8th and 10th days (each time, relevant tests were performed on the second day after treatment). The rats in the normal group and the model group were injected with 25 μL of normal saline into the intraarticular injections, and the rats in the magnesium boride group were injected with 25 μL of 100 μg / mL magnesium boride into the intraarticular injections. After the injections, the rats were gently placed back in the cage and waited for awakening.
[0069] Test and results:
[0070] (1) Mechanical pain threshold
[0071] Before modeling KOA rats, the mechanical pain threshold of each group of rats was measured as the basic pain threshold. The mechanical pain was measured on the second day after each drug treatment to detect the knee arthritis of drug-treated rats. The rats were placed in a transparent plastic box. After 30 minutes of adaptation, the rats began to be stimulated with von-Fery fibers on the right sole of the rat. The von-Fery fibers varied in thickness, including 1 g, 1.4 g, 2 g, 4 g, 6 g, 8 g, 10 g, and 15 g. First, the center of the sole of the right hind foot of the rat was found, and a certain force of 2 g of fiber was applied to make it bend. The stimulation lasted for 7 s. If the rat quickly lifted its right hind foot, it was recorded as a positive reaction (X). After waiting for 5 minutes, the von-Fery fiber with a lower weight of one gram was used to stimulate the rat until a negative reaction (O) occurred in the rat, that is, from X to O, and the stimulation was repeated 4 times. On the contrary, if the rat does not react when the center of the plantar of the right hind foot of the rat is stimulated with 2 g of von-Fery fiber, it is a negative reaction. Continue to stimulate the plantar of the rat with a fiber of one gram higher until the rat shows a positive reaction, from 0 to , and then continue to stimulate 4 times to complete the detection of the mechanical pain threshold of the rat. If the rat does not shrink its foot when stimulated with 15 g of fiber, the mechanical pain threshold of this rat is 15 g. If the rat shows a positive reaction when stimulated with von-Fery fiber less than 2 g continuously, the mechanical pain threshold of this rat is 0.25 g. The calculation formula of fiber sting pain is:
[0072] 50% g threshold=(10[ Xf+Kδ ]) / 10000.
[0073] Xf is the logarithm of the fiber weight used in the final stimulation of the rat, and K is obtained by looking up the table in Appendix 1 of “Quantitative assessment of tactile allodynia in the rat paw” (SR Chaplan et al., Journal of Neuroscience Methods 53 (1994) 55-63), and δ is 0.224.
[0074] according to Fig. 9 (a) and Fig. 9 (b) It can be seen that on the third day, the tingling pain of the fiber filaments in the model group and the magnesium boride group decreased significantly, indicating that the modeling was successful. The tingling pain of the fiber filaments in the magnesium boride group increased significantly after administration, indicating that magnesium boride has a therapeutic effect on arthritis.
[0075] (2) Heat pain
[0076] Before and after modeling of KOA rats, a plantar heat pain instrument was used to detect the rat's basal heat pain threshold and the heat pain threshold after modeling. The rat was placed in a transparent glass box and waited for half an hour until the rat's activity decreased. The temperature of the heat pain instrument was set to 55°C, aimed at the center of the rat's right hind foot, and the button was pressed to start automatic timing. If the rat retracted its foot, the heat pain instrument automatically detected the rat's retraction and stopped the heat stimulation, and the time when the rat retracted its foot was recorded. If the rat did not react, the heat light source automatically stopped after 30 s to avoid scalding the rat's foot. Rats with a repetition time of less than 4 s and greater than 30 s were eliminated. Each rat was stimulated 5 times, and then stimulated again after an interval of 5 min. The maximum and minimum heat pain thresholds were removed, and the average of these 3 data was calculated and used as the rat's heat pain threshold.
[0077] according to Fig. 9 (c) and Fig. 9 (d) It can be seen that on the third day of modeling, except for the normal group, the heat pain thresholds of other groups decreased significantly, indicating that the KOA model was successfully modeled. The heat pain threshold of the magnesium boride group gradually increased after administration, indicating that magnesium boride has a therapeutic effect on arthritis.
[0078] (3) Weight changes
[0079] The body weights of KOA rats were measured before modeling and on the afternoons of the 3rd, 5th, 7th, 9th, and 11th days after modeling. Fig. 9 (e) It can be seen that the weight of rats in the normal group gradually increased, and the weight of rats in the magnesium boride group increased more than that in the model group.
[0080] (4) Pathological tissue staining
[0081] The knee joints of rats in each group were removed and fixed in 4% paraformaldehyde for more than 4 hours. After dewaxing, dehydration, paraffin embedding and sectioning, hematoxylin-eosin (H&E) and safranin fast green (SO-FG) staining were performed. The recovery of knee cartilage injury was observed under an upright microscope with multiple magnifications, and images were collected at different magnifications. Fig.10 (a) It can be seen that the cartilage structure of the normal group is intact, chondrocytes are evenly distributed, and the number of inflammatory cells is small. The surface of the cartilage layer in the model group is not smooth, the chondrocyte clusters are unevenly distributed, and a large number of inflammatory cells appear. The staining of the magnesium boride group is relatively uniform, the chondrocyte clustering phenomenon is reduced, and the number of inflammatory cells is significantly reduced. SO / FG staining can intuitively reflect the structure of articular cartilage, subchondral bone and bone tissue, in which cartilage is red and osteogenesis is green. The cartilage tissue in the model group is reduced, and the cartilage tissue tends to be normal after drug administration.
[0082] Immunofluorescence of knee joint sections was performed using ColⅡ, MMP13, and IL-1β antibodies, and digital section scanning was performed. Fig.11Immunofluorescence of knee joint sections showed that the main inflammatory factor of arthritis IL-1β and articular cartilage destruction protein metalloproteinase MMP13 were significantly decreased in the magnesium boride group compared with the model group, while the expression of type II collagen, the main matrix of articular cartilage, was significantly increased in the magnesium boride group compared with the model group.
[0083] (5) Magnetic resonance imaging (MRI)
[0084] The rats were anesthetized with a small animal anesthesia machine and the knee joints of the rats were scanned by magnetic resonance imaging. The MRI images are shown in Fig.10 (b) According to Fig.10 (b) It can be seen that the white part in the frame of the normal group is the articular cartilage, while no obvious articular cartilage layer is seen in the model group, and the articular cartilage layer of the magnesium boride group is relatively clear, indicating that the articular cartilage of the magnesium boride group has been restored compared with the model group.
[0085] (6) Morphological observation
[0086] On the 14th day after the rat KOA model was established, the rats were anesthetized and the knee joints were taken for morphological observation. The rats were placed in a supine position on the operating table, the skin at the knee joint was disinfected, the skin at the right knee joint was cut, the excess tissue on the femur and tibia was removed, the knee joint was completely preserved, the bones were cut with surgical scissors, the excess blood stains on the knee joint were washed with saline, the knee joint was placed on a sterile non-woven cloth, and the knee joint was photographed. The results are shown in Fig.10 (c) It can be seen that the articular cartilage of the rats in the normal group was smooth, while the articular cartilage of the rats in the model group was swollen. In contrast, the articular cartilage of the rats in the magnesium boride group recovered to a certain extent.
[0087] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a two-dimensional magnesium boride sheet material, characterized in that: The preparation method is: The magnesium boride powder is ground to obtain magnesium boride particles, the magnesium boride particles are added to anhydrous ethanol, and then 1-butanol is added dropwise to form a suspension, a sodium chloride solution is added to the suspension, the suspension is stirred, and finally an ultrasonic treatment is performed to obtain a magnesium boride two-dimensional sheet material.
2. The preparation method according to claim 1, characterized in that: The ratio of the added amounts of the magnesium boride particles, anhydrous ethanol and 1-butanol is 500 mg: 50 mL: 5 mL.
3. The preparation method according to claim 1, characterized in that: The dropping speed of the 1-butanol was 0.1 mL / min.
4. The preparation method according to claim 1, characterized in that: The ratio of the added amount of the magnesium boride particles to the sodium chloride solution is 0.1 g:1 mL.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the sodium chloride solution is 0.9%.
6. The preparation method according to claim 1, characterized in that: The stirring is carried out at room temperature for 30 min.
7. The preparation method according to claim 1, characterized in that: The power of the ultrasound is 10 W; the time of the ultrasound is 10 min.
Citation Information
Patent Citations
Preparation method of magnesium boride nanosheet and application of magnesium boride nanosheet in Li-S battery diaphragm
CN115465870A
Preparation method of hydrogen production material, obtained hydrogen production material and application
CN116902914A
Method for preparing layered boron material through liquid phase method
CN107487776A
Medicament for tumor therapy and preparation method and application thereof,
CN109876008A